STRUGGLE OF SPARTAN TO MAINTAIN THEIR INDEPENDENCE IN 300 MOVIE BY ZACK NYDER (2007): A MARXIST APROACH - SASONGKO , BAYU (2011)
The research is proposed to analyze a struggle for slavery and colonization in a movie with the title 300 with Marxist Approach. There are two objectives: the first is to analyze the movie in term of structural elements, and the second is to analyze the movie based on Marxist Approach. This Research is a descriptive qualitative study, using the movie of Zack Snyder's 300 as the object of analysis of the style study. There are two kinds of data sources to be analyzed, namely primary and secondary. The primary data are the movie and script of the movie itself and the secondary data sources are some books, internet and articles related to the subject. The technique of data collection in this research is library research by summarizing, paraphrasing and documenting the data. In analyzing the data, the writer employs descriptive qualitative analysis Based on the analysis, the researcher draws two conclusions: The first is based on the structural analysis. The movie of Zack Snyder's 300 (2007) has interrelated structural elements which are related one another and also has solid unity. The Second is based on the Marxist analysis. Zack Snyder wants to reflect that freedom is the right of every human being. So, every people is entitled to get the same treatment in any forms.